2009
DOI: 10.1530/eje-09-0600
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CTLA-4 receptor an immunological marker of Graves' disease and severity of ophthalmopathy is associated with CTLA-4 Jo31 and CT60 gene polymorphisms

Abstract: Objective: Graves' disease (GD) is an autoimmune disorder with genetic and environmental background. CTLA-4 is a candidate gene for thyroid autoimmunity. Increased serum levels of soluble CTLA-4 (sCTLA-4) were found in some autoimmune diseases. Aim: The aim of the study was to evaluate the relation between sCTLA-4 level and clinical manifestation of Graves' ophthalmopathy (GO), thyroid status, and CTLA-4 gene polymorphisms. Design: Serum sCTLA-4 concentrations were determined in 93 GO patients and 93 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…Our results are in agreement with those of Oaks and Hallet (2000); Saverino et al (2007) and Daroszewski et al (2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with those of Oaks and Hallet (2000); Saverino et al (2007) and Daroszewski et al (2009).…”
Section: Discussionsupporting
confidence: 93%
“…The CT60 in the 3'UTR region of CTLA4 gene is the most promising locus for the autoimmune thyroid disease (Ban et al, 2005;Daroszewski et al, 2009). The meta-analysis study of Kavvoura et al (2007), shows consistent associations between Graves' disease and Hashimoto thyroiditis with CT60.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, sCTLA-4 production does not seem to be affected by disease evolution over time [49]. However, a recent study has shown that increased sCTLA-4 serum levels correlate with the severity of Graves' ophthalmopathy [33]. The discrepancy in these finding may be related to the greater number of GD patients enrolled in the later study (93 vs. 31).…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 94%
“…Linkage and association of the CTLA-4 exon 1 polymorphism with GD, and to lesser extent with HT, has been found in several populations, although there seems to be some inconsistency, probably due to population heterogeneity [11,17,27,[30][31][32][33] (Table 1).…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
See 1 more Smart Citation